Spillover effects of foreign monetary policy on the foreign indebtedness of banks and corporations - Paola Morales-Acevedo (Graduate Institute of International and Development Studies, 2019)
This paper analyses the impact of foreign monetary policy - from a broad range of countries - on the foreign indebtedness of Colombian banks and corporations, and evaluates if capital controls can help to mitigate these spillover effects. The paper uses two unique loan-level datasets on cross-border lending that cover all the foreign loans granted by foreign-located financial institutions to domestically located financial and non-financial companies, respectively. The results support the existence of spillover effects of foreign monetary policy over the characteristics of cross-border loans. In particular, periods of foreign monetary policy easing (tightening) are associated with: i) increases (decreases) on the cross-border lending to banks, and decreases (increases) on the cross-border lending to corporations; and ii) decreases (increases) on the loan interest rates to banks and corporations. The paper also finds that capital controls play an important role in mitigating these spillover effects, however, their effectiveness depends on the stance of both foreign and domestic monetary policy.
Keywords: E44; F34; G01; 330; cross-border lending; monetary policy; capital controls